‘For Me, Everything Was About the Continent’: Reimagining Gender Affects and Collectivity Through Daniela Catrileo’S Chilco 2023 - Bruna-Ramirez, R (SAGE Publications Ltd, 2025)
Our article brings together two seemingly dissimilar disciplines, philosophy of emotions and postcolonial literature, to analyse Mapuche writer Daniela Catrileo’s novel Chilco (2023). We argue that emotional contagion is a positive move in the novel, as it enables a decolonial, gender-based collectivity in light of Catrileo’s depiction of the colonial legacies in Chilco. Because we see Chilco as a political fiction under an inter- and transdisciplinary framework, our purpose is to analyse how Catrileo’s Chilco illustrates women’s collectivity in a decolonial narrative drawing from emotional contagion and gender studies. Our article has two sections. In ‘Connected body’, we draw on Chilean feminism to illustrate the experience of collectivity, delving into shared rage and joy. In ‘Connected discourses’, we draw on Magalí Armillas-Tyseira and Anne Garland Mahler, Audre Lorde and Gayatri Chakravorty Spivak to illustrate the post- and ongoing colonial discourses that are challenged in the novel. Catrileo’s novel unveils borderless and timeless notions of gender using a collective voice both in form and content. Finally, given the dialogic nature of the article, we reflect on our intersectional experience as women working in academia and in between the Global North and South. This article is triggered by fiction, but it is the result of personal experiences too. Writing the article together mirrors a feminist and decolonial practice that, although inexhaustive, may have potentially practical and gendered consequences for collective feminisms. © 2025 The Author(s).